Fear of covid-19 and covid-19 anxiety as predictors of adherence to treatment in patients with epilepsy - Sungur, Meltem; Arda Sürücü, Hamdiye; Köleoğlu, Şerife; Altay, Çimen (Health & Research Journal, 2023)
Background: The study aimed to examine fear of COVID-19 and Coronavirus Anxiety as predictors of adherence to treatment in individuals diagnosed with epilepsy during the COVID-19 pandemic. Method and Material: The study was carried out in a university hospital. The research sample consisted of 154 epilepsy patients. The patient identification form, Coronavirus (Covid-19) Fear Scale, Coronavirus Anxiety Scale, and the Medication Adherence Report Scale (MARS) were used as data collection tools. The data were shown as percentages and mean ± standard deviation (SD), and Pearson/Spearmen correlation and linear regression analyses were used to examine the relationship between the variables. Results: The results of the analysis demonstrated that the model established for medication adherence in epilepsy patients was significant (F: 12,892, p < 0.001). In addition, for medication adherence, COVID-19 anxiety (β = -0.312), regular drug use (β = 0.242), seizure frequency (β = -0.234), and accommodation in the city center (β = -0.173) were found to be statistically significant predictors (p < 0.001). It was found that the variables explained 24% of the total variance. Conclusions: It should be remembered that infectious diseases such as COVID-19 can reoccur and that it is necessary to be prepared for new contagious diseases likely to occur. In case of the recurrence of infectious diseases such as COVID-19, it is important to conduct interventional/experimental studies on how to increase medication adherence of patients and how to reduce COVID-19 anxiety.